The Governess of Penwythe Hall - Ladd, Sarah E. (Nashville, Tennessee : Thomas Nelson, 2019)
"In the first of a new series ... Delia, a governess to five recently orphaned children, would risk anything to protect them ... even her heart"--
Keywords: Governesses -- Fiction; Orphans -- Fiction; Guardian and ward -- Fiction; Inheritance and succession -- Fiction; Cornwall (England : County) -- Fiction -- History -- 19th century; Christian fiction; Regency fiction; Religious fiction; Romance fiction; Historical fiction